THE INFLUENCE OF ORGANIZATIONAL COMMITMENT ON EMPLOYEE KNOWLEDGE SHARING IN CLASS IIA METRO CORRECTIONAL INSTITUTIONS - Putri, Dea Himalia; Sebastian Iskandar, Irvan (Universitas Nusa Cendana, 2025)
The research aimed to find out the influence of organizational commitment on knowledge sharing at Class IIA Metro Correctional Institutions. Researchers used quantitative methods with data collection techniques; questionnaires were distributed to a sample of 81 employees at the Class IIA Metro Correctional Institution. Data analysis in this research used simple regression analysis, significance tests, and determination tests, with previously conducted validity, reliability, and normality tests. Based on the research results, there is a significant influence that occurs between organizational commitment and knowledge sharing. Then it can be seen from the research results that organizational commitment has an influence of 60.2% on knowledge sharing, and then the remaining 39.8% is influenced by other variables that are not in this research. Keywords: Organizational Commitment, Knowledge Sharing ; Employee ;Correctional Institutions